Nonverbal Communication Reconstruction on Facebook - Yuli Candrasari (Universitas Semarang, 2021)
Facebook provides users comfort in communicating even though they cannot see expressions or any other nonverbal signs, which have been an essential factor in supporting face-to-face communication. Therefore, this research is necessary because the absence of nonverbal communication, especially facial expression, touching, and gesture, renders the communication process between individuals ineffective and uncomfortable, as it was when people first used email to communicate via the internet. Through the study of Computer-Mediated Communication (CMC) perspectives, nonverbal communication, Social Presence Theory and Lack of Social Context Cues theory, this paper will discuss forms of nonverbal communication in the digital era. This study is based on research conducted by researchers using the netnography method and carried out through literature studies. The research was conducted on the Muslim community Bening Society on Facebook because the communication between them is very intense, as required in netnography. The loss of nonverbal communication in interpersonal communication does not, in fact, reduce netizens’ comfort in communicating and interacting. The emergence of digital emoticons and nonverbals is a substitute for nonverbal communication because digital emoticon and nonverbal functions in mediated interpersonal communication are the same as nonverbal communication.